Study of Pulmonary Hypertension in Patients Suffering from Chronic Obstructive Pulmonary Disease - TUDORAȘCU, D.R. (Curr Health Sci J, 2016)
ABSTRACT: Pulmonary hypertension (PAH) represents a frequent complication in patients suffering from chronic obstructive pulmonary disease (COPD), but the impact of accelerated inflammatory status on the pulmonary vascular bed is still insufficiently studied. Objectives: The study of the PAH's prevalence in patients suffering from COPD, its severity compared with lung function and the correlation with certain clinical, biological and functional parameters. Material and method: The study was performed on a group of 64 patients, average age 53 years, 42 of whom were men (65,62%), suffering from COPD who were admitted to the Emergency County Hospital Craiova, on the II-nd Medical Clinic, within a period of 18 months. When assessing the patients their clinical state was stable, without acute exacerbations items. The control group included 61 patients suffering from other diseases without inflammatory background, who were hospitalized in clinic in the same period. All the patients included in the study were evaluated by: physical examination, thoracic radiological examination, spirometry, inflammatory syndrome, echocardiography Doppler and oximetry. Results: The results of the study show a prevalence of 54.6 % PAH and a statistically significant impact of age, duration of the disease, Sa O2, inflammatory status, which was quantified in the study by ESR, serum levels of CRP and serum level of TNF alpha over the risk of developing COPD in patients suffering from PAH. Conclusions: The occurrence and the severity of PAH in patients suffering from COPD seems to be correlated with their age, duration of the disease, Sa O2 and serum levels of inflammatory markers.